ROUTE ALTERNATIVE FOR YOGYAKARTAâS RAILWAY DEVELOPMENT: DESIGN CHOICE AND POSSIBILITIES - , SAFRILAH, Prof. Ir. Sigit Priyanto M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Yogyakarta â Magelang track was closed in 1976. Currently, the ministry of transportation is reviewing reactivated possibilities to give this track its second chance. The research is aimed to provide some alternative routes between Yogyakarta-Magelang using MCA (Multi Criteria Analysis). MCAâs key feature is its ability to offers a number of ways of aggregating the data on individual criteria to provide indicators of the overall performance of options. Three alternative routes was decided with itâs each goal. First route crossing along the old track, second route connecting busy areas between Yogyakarta â Magelang, and the last alternative route heading straight to Borobudur Temple. Each route was analyzed with MCA method, comparing each route by scoring and weighting. Based on the analysis results, for quantitative criteria ( Construction cost, operational cost, land acquisition, and railway length) scoring and weighting given based on calculation using autocad civil 3D or simple Microsoft excel, and for qualitative criteria (demand, accessibility, landscape, social effect, and others) scoring and weighting given based on scale 1 â 5. And from the analysis using MCA, the third route has the highest weight, but weak in qualitative criteria and also has the highest cost. So the chosen route was the second route, with the best qualitative assessment and also cheap in quantitative assessment